2013
DOI: 10.1242/dev.094458
|View full text |Cite
|
Sign up to set email alerts
|

Porcn-dependent Wnt signaling is not required prior to mouse gastrulation

Abstract: SUMMARYIn mice and humans the X-chromosomal porcupine homolog (Porcn) gene is required for the acylation and secretion of all 19 Wnt ligands and thus represents a bottleneck for all Wnt signaling. We have generated a mouse line carrying a floxed allele for Porcn and used zygotic, oocyte-specific and visceral endoderm-specific deletions to investigate embryonic and extra-embryonic requirements for Wnt ligand secretion. We show that there is no requirement for Porcn-dependent secretion of Wnt ligands during prei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 93 publications
(147 reference statements)
3
49
0
Order By: Relevance
“…To assess the role of the epithelial Wnts in intestinal homeostasis, we used a floxed allele of Porcn that is null for Wnt secretion after Cre-mediated excision (Biechele et al, 2013;Proffitt and Virshup, 2012 (Korinek et al, 1998;Zhong et al, 2012). Unexpectedly, Porcn Del /Villin-Cre pups were viable, appeared phenotypically normal, and suckled and weaned without difficulty.…”
Section: Normal Intestine Homeostasis After Complete Inhibition Of Epmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the role of the epithelial Wnts in intestinal homeostasis, we used a floxed allele of Porcn that is null for Wnt secretion after Cre-mediated excision (Biechele et al, 2013;Proffitt and Virshup, 2012 (Korinek et al, 1998;Zhong et al, 2012). Unexpectedly, Porcn Del /Villin-Cre pups were viable, appeared phenotypically normal, and suckled and weaned without difficulty.…”
Section: Normal Intestine Homeostasis After Complete Inhibition Of Epmentioning
confidence: 99%
“…Porcn flox mice (Biechele et al, 2013) were backcrossed to C57BL/6 mice at least for six generations. Porcn flox mice were crossed with BL/6 Villin-Cre mice.…”
Section: Mouse Strains and Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our PCR arrays of human CC, we found that both CTBP1 and PORCN were highly upregulated ( Figure 1A). CTNNB1-CTBP activates transcription of pro-proliferative WNT target genes (47), whereas PORCN is required for the palmitoylation of WNT ligands, thereby regulating their secretion (48,49). Thus, we specifically inhibited either the CTNNB1-CTBP interaction or the activity of PORCN in human CC cells in vitro with the small molecule ICG-001 or C-59, respectively.…”
Section: Loss Of Macrophage-derived Wnt Inhibits CC Growth In Vivomentioning
confidence: 99%
“…Porcupine-mediated acylation of Wnts occurs at a conserved serine residue and is necessary for the secretion of the Wnt proteins that include this serine residue. Experimental perturbation of Porcupine interferes with secretion of all Drosophila Wnts (except for WntD, which lacks the target serine residue) and all mouse and human Wnts (26)(27)(28)(29). Small chemical inhibitors of Porcupine recently have been proposed to be efficient agents that interfere systemically with Wnt signaling in clinical applications; here we used the Porcupine inhibitor C59 (30)(31)(32).…”
Section: System-wide Perturbation Of Wnt Signaling By a Porcupine Inhmentioning
confidence: 99%